Italie obscure o Une terre pour les images? L’Italia artistico-letteraria di Bonnefoy e Orcel - Primo, Novella (Incontri. Rivista europea di studi italiani, 2021)
Italie obscure or Une terre pour les images? The Italian Art and Literature of Bonnefoy and Orcel Within the very wide panorama of contemporary French literature, Yves Bonnefoy (1923-2016) and Michel Orcel (born in Marseille in 1952) are two paradigmatic examples of the multi-faceted interest beyond the Alps towards Italy and its culture, evident in both writers as regards to essay writing, translation and the consequent metatraductive reflections, as well as in their creative productions. Despite the unavoidable differences in education and poetics, both scholars are comparable due to the common interest in the same Italian men of letters, for example Ariosto whose Orlando Furioso was translated by Orcel and finely interpreted by Bonnefoy — and particularly Leopardi, of whom both French authors have offered brilliant poetic translations and original essays. Considering some of their critical contributions to Italian art and literature (including Orcel’s, Italie obscure, 2001 and Bonnefoy’s, Une terre pour les images, 2005), the essay investigates the unique characteristics of the Italian landscape, on a natural and artistic level, which emerge from the writings of the two French authors so far examined.